2008
DOI: 10.1097/01.ogx.0000338104.02864.0f
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton Pump Inhibitors and Risk of Osteoporosis-Related Fractures

Abstract: O steoporosis is a common condition throughout the developed world, affecting up to 16% of women and 7% of men aged 50 years and older. 1 The presence of underlying osteoporosis is a major risk factor for the development of fractures of the hip, proximal femur, spinal vertebra and forearm. In 2000, the estimated number of people with fractures worldwide was 56 million, and about 9 million new osteoporotic fractures occur each year.2 In 1993/94, the number of hip fractures in Canada was 23 375.3 This number is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
5
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 6 publications
6
102
5
5
Order By: Relevance
“…As with Yang et al [10], a significant increase in the risk of hip fracture and trends with dose for both PPI and H 2 RA use were observed. However, the magnitude of effect was smaller in this study, and it did not demonstrate the same pattern of effects with cumulative use over time, as reported by Yang et al and Targownik et al, who conducted a case-control study within a Canadian administrative claims database [10,15]. Other than the study designs, the major difference between these studies was the choice of comparison group.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…As with Yang et al [10], a significant increase in the risk of hip fracture and trends with dose for both PPI and H 2 RA use were observed. However, the magnitude of effect was smaller in this study, and it did not demonstrate the same pattern of effects with cumulative use over time, as reported by Yang et al and Targownik et al, who conducted a case-control study within a Canadian administrative claims database [10,15]. Other than the study designs, the major difference between these studies was the choice of comparison group.…”
Section: Discussionmentioning
confidence: 41%
“…Other than the study designs, the major difference between these studies was the choice of comparison group. Both case-control studies [10,15] compared patients who had used acid-suppressive medication with those who had never used such drugs; whilst here, a time-dependent approach was used along with a comparison of current to past use in the acid-suppressant cohort. This allows the recency of exposure as well as intermittent use to be taken into account and reduces the likelihood of confounding by indication.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term use of PPIs significantly increases the risk of osteoporosisrelated fracture [30,31]. In our study, zoledronic acid showed significant increases in LS BMD versus risedronate in patients with history of PPI use at baseline in the prevention subpopulation with no differences in anti-TNF and SSRI patient subgroups, which were relatively small.…”
Section: Discussionmentioning
confidence: 67%
“…Although not all studies have supported an increased risk of fracture with ongoing PPI use [27], the strength of the association between hip fracture and PPI use has been shown previously to increase with the duration of PPI therapy over a 4-year period [28]. Similarly, a Canadian study showed that hip fracture risk progressively increased in PPI users after 5 years of therapy, and all osteoporotic fractures increased after 7 years of PPI therapy [29]. Our study shows a similar trend and extends this observation to a 10-year period.…”
Section: Discussionmentioning
confidence: 99%